Isolasi dan Karakterisasi Gen Pto Asal 20 Aksesi Anggrek Phalaenopsis - Elina, Juanita; Sukma, Dewi; ,, Giyanto; sudarsono, dan (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2017)
Bacterial soft rot disease because of Dickeya sp. infection is the main problem in Phalaenopsis production in Indonesia, but the percentage of infected plants has never been recorded in detail. Isolation and characterization of Pto gene from Phalaenopsis could be useful to support breeding for resistance Phalaenopsis. Encoding serine-threonine kinase, Pto gene confers resistance to bacterial infection of Pseudomonas syringae in tomato. The objectives of this study were to isolate, sequence and characterize fragment of Pto gene from 20 genotypes of Phalaenopsis (16 species and 4 hybrids) and to evaluate their molecular diversity. Genomic fragments of Phalaenopsis were amplified using Pto specific degenerate primers; and the PCR amplicons were sequenced. Searching the identity of determined sequences was done using BLAST against all accessions in NCBI GenBank DNA database and in Conserve Domain Database. PCR amplification using Pto specific primers produced a single DNA fragment of 500 bp. The determined nucleotide sequences from the amplicon were 449 bp. The nucleotide sequences of the amplicons from 20 Phalaenopsis genotypes showed high sequence identity to Pto from Musa acuminata. Translation of the amplicon results in 149 amino acid residues. Comparison of the translated polypeptides identify indicated there were low variations of Pto gene among accessions since they contain the PTO catalytic domain and the Serine/Threonine kinases, sub family of Interleukin-1 Receptor Associated Kinase (STK_IRAK) which are the conserved domains for PTO.Keywords: catalytic domain, disease resistance, fragment Pto gene, phylogenetic, RGA